The Role of Technology in Increasing the Competitiveness of SMEs in the Digital Era - Siregar, Eva Anzani; Wardi, Yunia; Marwan, Marwan (Electronic Journal of Education, Social Economics and Technology, 2025)
This study examines the role of digital technologies in enhancing the competitiveness of small and medium enterprises (SMEs) in the digital era using a Systematic Literature Review (SLR) approach. The findings highlight that digital transformation enables SMEs to accelerate innovation, expand collaboration networks, and improve operational efficiency. The adoption of technologies such as blockchain, e-commerce, and digital payment systems have positively impacted SMEs by increasing transparency, expanding market reach, and optimizing supply chains. However, challenges such as limited financial resources, lack of digital skills, and weak corporate governance hinder effective technology adoption. Government policies, collaboration with research institutions, and tailored digital strategies are essential to overcome these barriers. The study emphasizes the need for adaptive strategies to integrate Industry 4.0 technologies and sustain SME growth.